Infant wheeze, comorbidities and school age asthma. Issue 4 (11th April 2014) - Neuman, Åsa; Bergström, Anna; Gustafsson, Per; Thunqvist, Per; Andersson, Niklas; Nordvall, Lennart; Kull, Inger; Wickman, Magnus
Abstract Background Factors associated with early onset of wheeze have been described, but there is limited knowledge on which of these infant wheezers who will have developed asthma in school age. The aim was to identify clinical risk factors for asthma in the 8‐yr‐old children that wheezed during infancy in a population‐based setting. Methods Three thousand two hundred and fifty‐one children from a population‐based birth cohort followed prospectively from infancy until age 8 yr were included in the study. Data were analyzed using multivariate logistic regression analysis. Results Parents reported any wheeze episode before age 2 yr in 823 subjects (25%). Infant wheezers had an almost fourfold risk of asthma at age 8 [adjusted odds ratio (aOR) 3.68, 95% CI 2.74–4.96], equivalent to an asthma prevalence of 14% compared with 4% among non‐wheezers (p < 0.001). After adjustments for sex, exposure to tobacco smoke and indoor dampness/mould, allergic heredity (aOR 1.53, 95% CI 1.02–2.30), increased frequency of wheeze (aOR 3.41, 95% CI 2.09–5.56 for children with ≥3 episodes compared with ≤2 episodes during the first 2 yr of life), infant eczema (aOR 2.31, 95% CI 1.52–3.49), and recurrent abdominal pain (aOR 2.33, 95% CI 1.30–4.16) remained risk factors for school age asthma in the infant wheezing group. Conclusions Among infant wheezers, allergic heredity, increased severity of wheeze, infant eczema, and recurrent abdominal pain were independent risk factors for asthma at age 8 yr. Among children with three or four of these risk factors, 38% had asthma at school age.